Structural Sensitivity Analysis and Optimization 1 Linear Systems - Choi, Kyung K.; Kim, Nam-Ho (Mechanical Engineering Series, 2005)
Structural design sensitivity analysis concerns the relationship between design variables available to the design engineer and structural responses determined by the laws of mechanics. The dependence of response measures such as displacement, stress, strain, natural frequency, buckling load, acoustic response, frequency response, noise-vibration-harshness (NVH), thermo-elastic response, and fatigue life on the material property, sizing, component shape, and configuration design variables is defined through the energy principles (governing equations) of structural mechanics. In this 2-volume set, first- and second- order design sensitivity analyses are presented for static and dynamics responses of both linear and nonlinear elastic structural systems, including elasto-plastic and frictional contact problems. Book I Linear Systems introduces structural design concepts that include the CAD-based design model, design parameterization, performance measures, costs, and constraints. It also discusses design sensitivity analysis of linear structural systems, and discrete and continuum design sensitivity analysis methods. About the Authors: K.K. Choi is a Carver Professor of Mechanical Engineering at The University of Iowa. He teaches in the Mechanical and Industrial Engineering Department, and is a researcher in the Center for Computer Aided Design. His research area is in mechanical system analysis, design sensitivity analysis, and reliability based design optimization. He has authored numerous publications and has twice won the ASME Best Paper Award. He is an associate editor for four national and international journals, a fellow of ASME, and associate fellow of AIAA. N.H. Kim is an Assistant Professor in the Department of Mechanical and Aerospace Engineering at The University of Florida. His research area is in structural design optimization, design sensitivity analysis, nonlinear structural mechanics, structural-acoustics, and mesh-free method. Both authors are members of several professional societies including the American Society of Mechanical Engineers, American Institute of Aeronautics and Astronautics, the International Society for Structural and Multidisciplinary Optimization, and Society of Automotive Engineering.